Quantifying the Impacts of Coal Mining and Soil-Water Conservation on Runoff in a Typical Watershed on the Loess Plateau, China - Binbin Lin (MDPI AG, 2021)
Coal mining and soil-water conservation are the two major human interventions on the Loess Plateau in China. Analyzing their impacts on hydrological processes is of great significance for sustainable water resource management. Using hydrological simulation (Soil and Water Assessment Tool, SWAT) and a data-driven method (double mass curve, DMC), the contributions of these two human activities and climate change to the runoff decrease were analyzed in the upper Fenhe River. The runoff in the three affected periods (1967–1987, 1988–1994, and 1995–2017) decreased by 7.5%, 28.2%, and 24.1%, respectively, compared with the base period (1957–1966). In the first affected period (1967–1987), the amount of coal mining activities was small, human activities had little impact on runoff. In the second (1988–1994) and third (1995–2017) periods, as the coal mining and soil-water conservation intensified, their contributions to the runoff decrease rapidly increased. Due to the uncertainties in the model structure and parameters, in addition to the impact of the data accuracy, the results obtained from the two methods were different, but the proportions and the trends of the contribution rates in the different periods were consistent.